Ação social no contexto da Pastoral Universitária: contribuições formativas ao jovem universitário numa perspectiva humanizadora - Guedes, Walkíria Ferreira (2023)
The present study proposes to analyze the formative contributions that collective social actions, carried out within the scope of the Pastoral Universitária, in the period between 2007 and 2016, made possible for the young university student of a Community University in São Paulo. We start from the interest in identifying the possibilities for social actions to contribute as educational practices in the formation of young university students for humanization and solidarity with the other. University extension activities make up one of the dimensions of the university, and, as of 2018, according to Resolution CNE/CES, nº 7, they became mandatory as part of the curricular matrix of undergraduate courses. It is believed that the social actions developed in the context of the University Pastoral are concrete possibilities for the involvement of young graduates with the reality around the university, in vulnerable territories. Such actions are also capable of stimulating social experiences and knowledge production outside the academic environment, helping students to know the reality of other subjects in the dialectic processes of exclusion, awakening critical-reflexive capacity. This also makes possible formative contributions for a more solidary humanization in the encounter with the reality of denial of the human person. It seeks to rescue the importance of social actions as educational practices associated with the academic training of young graduates. The bibliographic and documentary study was central to the contributions of several authors, including: Arroyo (2014; 2013), Assmann (2002; 2001; 2000), Chizzotti (2017), Feldmann (2017; 2016; 2013; 2009), Francisco ( 2020; 2015; 2013), Freire (2011; 2005; 1996), Ghanem, Trilla (2008), Gohn (2020; 2022; 2016; 2010), Ianni (1996), Sacristàn (2008; 2002; 2000; 1999) and Documents of the Church's Magisterium and Social Doctrine. The purpose of this research was inspired by the paradigm of dialectics, therefore, a qualitative approach was chosen, because we start from the assumption that there is a dynamic relationship between the real world and the subject, between the subject and the object. The empirical research was mediated by contact with the participating subjects, according to selection criteria. In all there were 11 (eleven), 10 (ten) students and 01 (one) advisor, who were involved in the planning and carrying out of university pastoral activities in the period between 2007 and 2016. interview with a semi-structured script of questions. The research data showed that social actions in the context of the University Pastoral can be configured in a proposal of educational action, pedagogical practice that contributes to the formation of young university students, awakening them to a culture of encounter in the perspective of solidary humanism